Measurements of HbA1c for Patients with Diabetes Mellitus and Foot Ulceration - Mohammed A.Taher; Mayada M. Moustafa; Aqeel S. Mahmood (College of Pharmacy University of Baghdad, 2017)
People with diabetes can develop different foot problems. In the blood stream glucose reacts with hemoglobin to make a glycosylated hemoglobin molecule called hemoglobin A1c or HbA1c, the more glucose in the blood the more hemoglobin A1c will be present in the blood. The HbAlc test is currently one of the best ways to check diabetes to be under control.  The aim of study is to compare between the blood investigations which includes the fasting blood sugar and HbAlC (glycosylated hemoglobin), and to evaluate the benefit of  HbAlc (measurement for diabetic patients with foot ulcer,  to be a good indicator for controlling blood glucose). Sixty patients with type2 diabetes mellitus from the outpatient clinic of Baghdad Teaching Hospital, Medical City over the period from Nov. 2006 to Nov. 2008, were included in the study. Follow up was done only to 30 patients with diabetic foot ulcer. Twenty (66.66%) were males and 10(33.33%) were females their age range from (23-75) years (mean age of 52years), and 21 normal subjects as control. A (Glycohemoglobin HbAl-Test/fast lon-Exchange Resin Separation Method) kit was used. The data finding that there is a greater association between HbAlc level and foot ulceration healing. There is a relationship between the age of the patients and the HbAlc level. The patients who used (Glibenclamide+Metformin) have the lower range of HbAlC, while those who use (Metformin) have the higher level of HbAlc. HbAlc (glycosylated hemoglobin) is most accurate test to determine actual reading over the past 2-3 months, and to evaluating the risk of glycemic damage to the tissues. So, we recommend the HbAlc testing, but it can't be used to monitor day-to-day blood glucose concentration because it's not influenced by fluctuation in blood concentration. Key words: Diabetic foot ulcer, HbAlc